Influence of COD/SO42– Ratios on Performance of Anaerobic Hybrid Reactor and Up-Flow Anaerobic Sludge Bed Reactor - Demirci1, Yavuz; Saatci2, Yusuf (Asian Journal of Chemistry, 2013)
This study was carried out to be able to provide possible key parameters for the best performance of anaerobic hybrid reactor and up-flow anaerobic sludge bed reactor (UASBR). Laboratory-scale (1.70 L) anaerobic hybrid reactor and UASBR were operated at chemical oxygen demand (COD) to sulfate (SO42-) ratios of 25, 15, 10, 7 and 5 in a 155-day period to evaluate the effects of the presence of sulfate on the reactor performance. The results showed that when COD/SO42- ratios changed from 25 to 5 with increasing sulfate concentration from 400 to 2130 mg/L, slight decreases both in conversion ratios of removed chemical oxygen demand to methane and chemical oxygen demand removal efficiencies were observed. However, with decreased COD/SO42-, methane production rate decreased considerably and sulfate removal efficiencies increased. For UASBR, the methane production rate decreased as much as about 59 % and high sulfate removal efficiencies were obtained at COD/SO42- ratio of 5. Chemical oxygen demand removal efficiencies and biogas produced from the anaerobic hybrid reactor were always higher compared to those obtained with UASBR.